2004
DOI: 10.1002/jcc.20145
|View full text |Cite
|
Sign up to set email alerts
|

Junmei Wang, Romain M. Wolf, James W. Caldwell, Peter A. Kollman, and David A. Case, "Development and testing of a general amber force field"Journal of Computational Chemistry(2004) 25(9) 1157–1174

Abstract: In the online and published versions, equation (5) appeared incorrectly. The correct version appears below. We would like to extend our sincere apologies for any confusion this may have caused.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
3,654
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 3,089 publications
(3,676 citation statements)
references
References 0 publications
19
3,654
0
3
Order By: Relevance
“…22 The bonded and nonbonded parameters were adopted from the general Amber force field (GAFF). 23 Preliminary simulations in aqueous solution showed that the coumarin groups of BPC tend to form π-π stacked structures with the naphthol unit, which is in accordance with the NMR observations. Based on this fact we constructed the 1:1 hostguest structure of BPCY for MD simulations in aqueous solution and the final structure of this 1:1 host-guest complex BPCY is shown in Figure 4.…”
Section: Resultssupporting
confidence: 80%
“…22 The bonded and nonbonded parameters were adopted from the general Amber force field (GAFF). 23 Preliminary simulations in aqueous solution showed that the coumarin groups of BPC tend to form π-π stacked structures with the naphthol unit, which is in accordance with the NMR observations. Based on this fact we constructed the 1:1 hostguest structure of BPCY for MD simulations in aqueous solution and the final structure of this 1:1 host-guest complex BPCY is shown in Figure 4.…”
Section: Resultssupporting
confidence: 80%
“…23 In this approach, we used the average induced surface charge density (ISCD), σ i , obtained from a boundary element solution of the Poisson equation to derive a simple linear correction to the van der Waals radius to obtain the Born radius, r i Born , for each atom, i, of a molecule. 23 To obtain the σ i for eq 3, all atoms are initially assigned Born radii equal to the General AMBER Force Field (GAFF) 39 van der Waals radii r i 0 . From the boundary element solution to the Poisson equation, the average ISCDs for each atom are then calculated by assigning the surface patches and their associated charge density to the nearest atom.…”
Section: Theory and Implementationmentioning
confidence: 99%
“…All initial structures were taken from molecular docking. Force field parameters for the nonprotein atoms (dienophiles and diene) were generated from the general Amber force field (gaff), [62] using the Antechamber program. The generation of gaff-parameters was based on AM1 geometries, and the AM1-BCC approach was used for partial charges.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%